2006
DOI: 10.1124/jpet.106.105270
|View full text |Cite
|
Sign up to set email alerts
|

Extended Access to Nicotine Self-Administration Leads to Dependence: Circadian Measures, Withdrawal Measures, and Extinction Behavior in Rats

Abstract: The present study characterized nicotine intake, circadian patterns of food and water intake, precipitated somatic signs of withdrawal, and extinction of nicotine-seeking behavior in rats with 23-h access to intravenous self-administration (IVSA). Separate groups of animals were allowed access to nicotine IVSA (0.015, n ϭ 9; 0.03, n ϭ 14; 0.06, n ϭ 16; mg/kg/0.1 ml infusion/s; fixed ratio 1) and trained to nosepoke for food and water 23 h/day for 40 consecutive days. Somatic signs of nicotine withdrawal were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 50 publications
12
112
1
Order By: Relevance
“…It has long been proposed that responding during extinction sessions may provide a measure of the incentive-motivational properties of the drug (Markou et al 1993). Recent nicotine studies using an extended (23 h/day) access of self-administration paradigm showed that levels of extinction responding remained higher in rats receiving the highest dose (0.06 mg/kg/infusion) of nicotine compared to rats trained with lower doses (O'Dell et al 2007) and that although the first day extinction responding did not vary as a function of total nicotine infusions/intake, there was a positive correlation of extinction with nicotine infusions earned during the first 2 h of the extended access (Harris et al 2007). Moreover, a cocaine study reported that drug-seeking responding in rats trained to selfadminister higher doses of cocaine were more resistant to extinction than in rats on a lower dose (Valles et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been proposed that responding during extinction sessions may provide a measure of the incentive-motivational properties of the drug (Markou et al 1993). Recent nicotine studies using an extended (23 h/day) access of self-administration paradigm showed that levels of extinction responding remained higher in rats receiving the highest dose (0.06 mg/kg/infusion) of nicotine compared to rats trained with lower doses (O'Dell et al 2007) and that although the first day extinction responding did not vary as a function of total nicotine infusions/intake, there was a positive correlation of extinction with nicotine infusions earned during the first 2 h of the extended access (Harris et al 2007). Moreover, a cocaine study reported that drug-seeking responding in rats trained to selfadminister higher doses of cocaine were more resistant to extinction than in rats on a lower dose (Valles et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, clinical literature shows that feelings of relief upon smoking are greater in heavy, when compared to light smokers (Parrott 1994(Parrott , 2000Adan et al 2004) and suggests that conditioned responses to drug cues are positively correlated with the degree of alcohol dependence (Glautier and Drummond 1994;George et al 2001). Recent animal studies using the 23 h/day self-administration paradigm showed that lever responding in the first extinction session was positively correlated with nicotine infusions earned during the first 2-h of self-administration (Harris et al 2007) and seemed more resistant to extinction in animals on higher compared to lower doses of nicotine (O'Dell et al 2007). Cue-induced reinstatement of 3,4 methylenedioxymethamphetamine (MDMA; an amphetamine derivative)-seeking in rats was positively correlated to the responses made during prior self-administration training (Ball et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rodents will increase intravenous or oral self-administration of drugs with extended access to the drugs and during withdrawal from the dependent state, measured both by an increased amount of drug administration and working exponentially harder to obtain the drug in progressive-ratio schedules of reinforcement. Such increased self-administration in dependent animals has been observed with cocaine, methamphetamine, nicotine, heroin, and alcohol (Ahmed and Koob, 1998;Ahmed et al, 2000;Roberts et al, 2000;Breese et al, 2005;Kitamura et al, 2006;O'Dell et al, 2007).…”
Section: Sex Differences In Drug Abusementioning
confidence: 99%
“…That is, unlike the current experimental arrangement, patterns of human tobacco use are not typically continuous but are instead intermittent throughout the waking hours. Thus, further research with methods that may more closely model extended, intermittent human exposure to tobacco (e.g., O'Dell et al, 2007 ) may also be necessary to generalize the current time-related dissipation of the reinforcement enhancement to human behavior. Additionally, the current dose of nicotine delivered via osmotic minipump (3.16 mg/kg/day) reportedly results in plasma levels of 44 ng/ml ( Kenny et al, 2003 ), but other reports have variable estimates of plasma levels from similar doses and route of administration ( Ghosheh, Dwoskin, Miller, & Crooks, 2001 ;LeSage et al, 2002 ;Lockman et al, 2005 ;Nguyen, Rasmussen, & Perry, 2004 ).…”
Section: Nicotine and Tobacco Researchmentioning
confidence: 99%